REDESAIN WEBSITE E-COMMERCE PADA PERUSAHAAN PENJUALAN KOPI MENGGUNAKAN METODE WATERFALL - Lina Noviana; Francka Sakti Lee (ISTEK WIDURI, 2026)
Previously, the company’s website functioned only as a static company profile and was unable to facilitate online sales transactions. This limitation affected market expansion opportunities and reduced the efficiency of sales data management. This study aimed to redesign the website interface and develop an e-commerce system to address these issues. The research applied the waterfall method, which consists of the analysis, design, implementation, testing, and final system stages. The result of this development is an integrated e-commerce website that supports independent customer transactions, including product exploration, shopping cart management, checkout, payment processing, and order tracking. Based on the conducted testing and user evaluation, the developed system was able to operate properly and support digital transaction activities more effectively. The redesign of the website successfully transformed the company profile platform into a functional e-commerce system that is more interactive and structured.